Unusual presentation of antiphospholipid antibody syndrome in ayoung male: Diagnostic and therapeutic challenge (Indian Journal of Case Reports, 2026)
The acquired autoimmune thrombophilia known as antiphospholipid syndrome (APS) or antiphospholipid antibody syndrome is defined by arterial or venous thrombosis in the presence of persistent antiphospholipid antibodies. APS in young guys is uncommon and frequently underdiagnosed because of unusual presentation and multisystem involvement, whereas it is more frequently observed in females, particularly accompanying maternal morbidity, acute abdominal distension, jaundice, and black urine. These were the symptoms observed in a 35-year-old male patient who had no past comorbidities. Massive ascites and hepatocellular dysfunction were found upon examination. Investigations revealed conjugated hyperbilirubinemia, significantly increased liver enzymes, positive lupus anticoagulant, and negative anticardiolipin and anti-β2 glycoprotein I antibodies. Imaging showed severe portal vein thrombosis that extended into the splenic and superior mesenteric veins with mesenteric ischemia, as well as Budd-Chiari syndrome with hepatic vein non-opacification. The patient had hepatic vein stenting after receiving therapeutic anticoagulation with low molecular weight heparin right away. He was switched to acenocoumarol for long-term oral anticoagulation.